Kaehlerian manifolds admitting a metric semi-symmetric F-connection-II - Purane, S G (Recent Research in Science and Technology, 2012)
In Kaehlerian space of real dimension n a semi-symmetric F-connection was introduce by S.S.Pujar[2] about one decade ago. Using this affine F-connection we obtain some global results. The main purpose of the paper is to establish that a conformally flat real Kaehlerian manifold is W-flat if and only if the curvature tensor of the metric semi-symmetric F-connection vanishes.